Skip to content

Add rrule for spdiagm #5

Add rrule for spdiagm

Add rrule for spdiagm #5

Triggered via pull request October 12, 2023 18:38
Status Cancelled
Total duration 1m 51s
Artifacts

format.yml

on: pull_request
Fit to window
Zoom out
Zoom in

Annotations

1 error and 5 warnings
format
Process completed with exit code 1.
format: src/rulesets/SparseArrays/sparsematrix.jl#L141
[JuliaFormatter] reported by reviewdog 🐶 Raw Output: src/rulesets/SparseArrays/sparsematrix.jl:141:- src/rulesets/SparseArrays/sparsematrix.jl:142:-function rrule(::typeof(spdiagm), m::Integer, n::Integer, kv::Pair{<:Integer,<:AbstractVector}...) src/rulesets/SparseArrays/sparsematrix.jl:143:- src/rulesets/SparseArrays/sparsematrix.jl:152:+function rrule( src/rulesets/SparseArrays/sparsematrix.jl:153:+ ::typeof(spdiagm), m::Integer, n::Integer, kv::Pair{<:Integer,<:AbstractVector}... src/rulesets/SparseArrays/sparsematrix.jl:154:+)
format: src/rulesets/SparseArrays/sparsematrix.jl#L164
[JuliaFormatter] reported by reviewdog 🐶 Raw Output: src/rulesets/SparseArrays/sparsematrix.jl:164:-
format: src/rulesets/SparseArrays/sparsematrix.jl#L168
[JuliaFormatter] reported by reviewdog 🐶 Raw Output: src/rulesets/SparseArrays/sparsematrix.jl:168:- return Tangent{typeof(p)}(second = d) src/rulesets/SparseArrays/sparsematrix.jl:169:-end src/rulesets/SparseArrays/sparsematrix.jl:178:+ return Tangent{typeof(p)}(; second=d) src/rulesets/SparseArrays/sparsematrix.jl:179:+end
format: test/rulesets/SparseArrays/sparsematrix.jl#L35
[JuliaFormatter] reported by reviewdog 🐶 Raw Output: test/rulesets/SparseArrays/sparsematrix.jl:35:- ∂a_fd, ∂b_fd, ∂c_fd = j′vp(_fdm, (a, b, c) -> spdiagm(0 => a, 1 => b, 0 => c), ȳ, a, b, c) test/rulesets/SparseArrays/sparsematrix.jl:35:+ ∂a_fd, ∂b_fd, ∂c_fd = j′vp( test/rulesets/SparseArrays/sparsematrix.jl:36:+ _fdm, (a, b, c) -> spdiagm(0 => a, 1 => b, 0 => c), ȳ, a, b, c test/rulesets/SparseArrays/sparsematrix.jl:37:+ )
format: test/rulesets/SparseArrays/sparsematrix.jl#L56
[JuliaFormatter] reported by reviewdog 🐶 Raw Output: test/rulesets/SparseArrays/sparsematrix.jl:56:- ∂a_fd, ∂b_fd, ∂c_fd = j′vp(_fdm, (a, b, c) -> spdiagm(M, N, 0 => a, 1 => b, 0 => c), ȳ, a, b, c) test/rulesets/SparseArrays/sparsematrix.jl:58:+ ∂a_fd, ∂b_fd, ∂c_fd = j′vp( test/rulesets/SparseArrays/sparsematrix.jl:59:+ _fdm, (a, b, c) -> spdiagm(M, N, 0 => a, 1 => b, 0 => c), ȳ, a, b, c test/rulesets/SparseArrays/sparsematrix.jl:60:+ )